Party makers enterprise / Mohd Shaiful Zahari Sallehudin ... [et al.] - Sallehudin, Mohd Shaiful Zahari; Ibrahim, Muhammad Azwan Shah; Sulaiman, Syafiq Adhwa; Khairuddin, Muhammad Ali Imran (2017)
Reason for Choice of Business: • To establish and operate party events for the people who are living in Shah Alam area. • To provide with the friendliest services with affordable prices of services.